A randomized phase II study to determine the efficacy and tolerability of two doses of eribulin plus lapatinib in trastuzumab pre-treated patients with Her2-positive metastatic breast cancer - E-Vita - - Bischoff, Joachim; Marmé, Frederik (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Lapatinib (L) in combination with capecitabine has been approved for the treatment of HER2+ advanced breast cancer (ABC) progressed after anthracycline-, taxane-, and trastuzumab (T)-containing therapies. The use is limited by overlapping toxicities. Therefore, other combinations of L with less toxic agents are needed. In the E-VITA study two schedules of Eribulin (E) in association with L have been investigated.Methods: E-VITA (NCT01534455) is a randomized phase II study to determine the efficacy and tolerability of two doses of E plus L in T pre-treated pts with HER2+ ABC. Main eligibility criteria were: ABC not suitable for surgery or radiotherapy alone; adjuvant and up to 3 chemotherapy regimen for ABC. Pts were randomized (1:1) to receive E 1.23mg/m2 iv d1,8 q21 (E1.23)...
Gesehen am 09.11.2017